2005
DOI: 10.1016/j.jasms.2005.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between sodium dodecyl sulfate micelles and peptides during matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) of proteolytic digests

Abstract: Although sodium dodecyl sulfate (SDS) is routinely used as a denaturing agent for proteins, its presence is highly detrimental on the analysis of peptides and proteins by mass spectrometry. It has been found, however, that when SDS is present in concentrations near to or above its critical micelle concentration (CMC), improvements in the matrix-assisted laser desorption/ ionization mass spectrometry (MALDI-MS) analysis of peptide mixtures or hydrophobic proteins are obtained. To elucidate possible explanations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…Probably, this ionization process improvement is due to the presence of a higher number of protein sites available on the polypeptide chains surface, as a function of the oligomeric dissociation and partial protein unfolding, originated by the significant interaction between HbGp and CTAC at pH 7.0. Improvement of MALDI signals for hydrophobic peptides, obtained from digestion of several proteins, in the presence of surfactants has been also previously reported [34]. On the other hand, the intensity of the double-protonated peaks associated to the Linker and monomer chains is decreased, when compared with previous work focusing native HbGp in the absence of surfactants [12].…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…Probably, this ionization process improvement is due to the presence of a higher number of protein sites available on the polypeptide chains surface, as a function of the oligomeric dissociation and partial protein unfolding, originated by the significant interaction between HbGp and CTAC at pH 7.0. Improvement of MALDI signals for hydrophobic peptides, obtained from digestion of several proteins, in the presence of surfactants has been also previously reported [34]. On the other hand, the intensity of the double-protonated peaks associated to the Linker and monomer chains is decreased, when compared with previous work focusing native HbGp in the absence of surfactants [12].…”
Section: Resultssupporting
confidence: 59%
“…In the surfactant concentration range used in this work, SDS decreases, but does not to prevent completely, the sample ionization process [34,36], which has been a problem found previously by other researchers employing this technique. The analysis by MALDI-TOF-MS allowed us to obtain spectrometric data of sufficient intensity to evaluate the surfactant effect upon HbGp, especially at 0.2 mM of SDS.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This was not the case for solvent-based MALDI analysis using traditional acidic aqueous/organic solvent conditions, which resulted in severe over-representation of hydrophilic peptide (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11) and provided no spectra for insoluble amphiphilic peptide even when present at 50% relative molar amount. Less accurate representation of components in mixtures by the traditional method appears to be a combination of poor dissolution of peptides in the solvent and preferential ionization of more hydrophilic peptides in the mixture.…”
mentioning
confidence: 99%
“…In contrast, some research groups have reported that SDS aids the MALDI‐MS analysis 12–15. The MALDI signal intensity for the SDS‐containing protein solutions was recovered by raising the SDS concentration of the sample to above 0.3%, which is near its critical micelle concentration (CMC) 12.…”
mentioning
confidence: 97%